ESTUDO DA MOAGEM CRIOGÊNICA DE ALTA ENERGIA DO FERRO, CROMO E NIÓBIO SEGUIDA DE TRATAMENTOS TÉRMICOS - Silva, Alisson Kwiatkowski da (2015)
Iron, chromium and niobium nitrides exhibit very interesting physical, chemical, electrical and/or magnetic properties both from the theoretical point of view and from the applications perspectives. Among the applications, these nitrides have found significant interest as materials for magnetic storage devices or in coating industry. The Fe-N, Cr-N and Nb-N systems consist of several interstitial solutions (α, γ, ε-FexN), chemical compounds (γ’-Fe4N, ζ-Fe2N, Cr2N, CrN, β-Nb2N, γ-Nb4N3, δ-NbN, ε-NbN) and metastable phases (α’ martensite, α”-Fe16N2, δ’-NbN). The present work investigates the viability of nitriding of iron, chromium and niobium powders by high energy cryogenic milling, i.e., the high energy milling of metal powders in liquid nitrogen, that accelerate the fracture process, as compared with the convention technic, and allows that the steady state of milling be reached quickly. In addition, some studies suggest the possibility of nitrogen introduction to the metallic powder during milling. In order to assess the nitriding possibility, iron, chromium and niobium powders were processed by high energy cryogenic milling during different milling times (0,5 h, 1,0 h, 2,0 h and 4,0 h). The milled powders were subsequently characterized by DTGA, DSC, TMA, FEG-SEM and DRX. The iron powder was compacted and sintered at 1200ºC during 1 h (N2 atmosphere), and the samples characterized by optical microscopy, SEM, WDS, Mossbauer spectroscopy, DRX, MFM and nanohardness. The chromium and niobium powders processed during 2 h by high energy cryogenic milling was compacted and sintered, respectively, at 1200ºC and 1300ºC during 1 h (N2 atmosphere), and the sample characterized by DRX. The results suggests that the iron powder can’t be nitrided by high energy cryogenic milling even after heat treatment in nitrogen atmosphere. By the other hand, chromium nitrides can be obtained after heat treatment in nitrogen atmosphere (high temperature nitration) and niobium nitrides can be obtained after heat treatment both in nitrogen and argon atmosphere.